PENGARUH KEPUASAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BINTANG TERANG PEKANBARU - Ardianti Risa; Marzolina Marzolina; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of the study was to determine the effect of job satisfaction, workdiscipline and motivation on employee performance. The location of this researchwas carried out at PT Bintang Terang Pekanbaru. The population in the studyamounted to 44 people, because the total population was less than 100, the entirepopulation in the study was sampled using the census method. Data analysis inthis study used multiple linear regression. The results of the study explain that jobsatisfaction has a significant effect, as well as work discipline has a significantinfluence and motivation also has a significant effect on employee performance atPT Bintang Terang Pekanbaru. Simultaneously, the variables of job satisfaction,work discipline and motivation have a significant influence on employeeperformance variables. While the adjusted R Square value of 0.640 explains thatthe variables of job satisfaction, work discipline and motivation can affectemployee performance variables at PT Bintang Terang Pekanbaru by 64% whilethe remaining 36% is influenced by other variables not examined in this study. Keywords: Job Satisfaction, Work Discipline, Motivation and Performan